2021
DOI: 10.2174/1871526520666200609121400
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Cystic Echinococcosis and Toxocariasis in Urmia Municipal Workers, Northwest Iran

Abstract: Background: Echinococcus granulosus and Toxocara spp. the causative agents of hydatid cyst and toxocariasis in human and animals, are zoonotic infection with medical and veterinary significance respectively. Aim: Herein, we aimed to investigate the seroprevalence of toxocariasis and cystic echinococcosis in Urmia municipal workers (gardeners and sweepers) in 2018 using ELISA assay. Objective: There is no precise report on the seroprevalence of toxocariasis and cystic echinococcosis in Urmia municipal worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In Iran, the highest prevalence of hydatid cysts in humans, as well as the highest rate of Echinococcus infection in the final hosts (mainly dogs), has been reported in the southern regions of the country [ 1 ]. In a study by Asadi et al, on 220 municipal workers in Urmia, northwestern Iran, anti-hydatid cyst antibodies were detected in 2.3% of the studied individuals [ 2 ]. In two recent studies conducted in Fars province, southern Iran, the seroprevalence of hydatid cyst among children living in a rural area and blood donors was reported to be 6.7 and 5.6%, respectively [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the highest prevalence of hydatid cysts in humans, as well as the highest rate of Echinococcus infection in the final hosts (mainly dogs), has been reported in the southern regions of the country [ 1 ]. In a study by Asadi et al, on 220 municipal workers in Urmia, northwestern Iran, anti-hydatid cyst antibodies were detected in 2.3% of the studied individuals [ 2 ]. In two recent studies conducted in Fars province, southern Iran, the seroprevalence of hydatid cyst among children living in a rural area and blood donors was reported to be 6.7 and 5.6%, respectively [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shafei et al in North Khorasan Province in northern Iran reported a 3.96% prevalence among 932 referred individuals (12). In another study on 220 municipal workers in the northwest of Iran by Asadi et al, the seroprevalence of cystic echinococcosis was estimated at 2.3% (13). The ELISA test was used in most studies due to its high performance, acceptable sensitivity and specificity, and cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%